EFFECTIVENESS OF VIDEO AND BOOKLET MEDIA EDUCATION ON THE KNOWLEDGE, ATTITUDES AND BEHAVIOR OF PREGNANT WOMEN REGARDING GESTATIONAL DIABETES AT BANGKALA HEALTH CENTER, MAKASSAR CITY - Haruna, Sri Rahmah; Suriyati, Yayat; Juhaeriah, Juju (Universitas Islam Negeri Alauddin Makassar, 2025)
Gestational diabetes is one of pregnancy complication. This research aims to determine the effectiveness of video and booklet media education on the knowledge, attitudes and behavior of pregnant women about gestational diabetes at the Bangkala Community Health Center, Makassar City. The research design used is quasi experimental, namely using a pretest and posttest two group design. The population for this research is the average number of pregnant women who visit ANC at the Bangkala Health Center every three months from May-July 2023, namely 149 people. The data collection technique was purposive sampling with a total sample of 60 respondents. The analysis used several statistical tests, including Wilcoxon, Mann-Whitney, and Independent T Test. The results of the research showed that the effectiveness of video media on knowledge was 97.38% and was in the effective category, while the effectiveness of booklet media was 83.34% and was in the effective category. The effectiveness of video media on attitudes was 81.91% and was in the effective category, while the effectiveness of booklet media was 58.47% and was in the category effective enough. The effectiveness of video media on behavior is 88.77%, which is in the effective category, while the effectiveness of booklet media on behavior is 91.07% and is in the effective category. Conclusion: The effectiveness of video and booklet media is not significantly effective in increasing the knowledge of pregnant women with an effect size of 0.03. The effectiveness of Video and Booklet media is significantly ineffective for the attitudes of pregnant women, or in other words, it has a small effect size with a value of 0.23. The effectiveness of Video and Booklet media is significantly ineffective for the behavior of pregnant women with a large effect value of 0.25. It is recommended that future researchers be able to examine the effect of the education provided on increasing blood glucose levels in pregnant women after the intervention